HARBIY DISKURS TUSHUNCHASI VA HARBIY SOHADAGI AHAMIYATI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
In this article, the importance of military discourse in the military sphere, how wide it is, military terms, jargons, abbreviations, and similar processes, and the role of military discourse in similar processes are considered. Information was also given about what military discourse is and its meaning.
Keywords: Military discourse, terminology, shorthand, jargon, code, linguistics, military communication, manipulation, national security.